Analisis Hukum Islam terhadap Putusan Hakim tentang Perceraian Campur Tangan Orang Tua di Pengadilan Agama Belopa - Irawan, Muhammad Rafly Irawan; Hamzah K; Anita Marwing; Asni Zubair (LP2M IAIN Palopo, 2025)
The aim of this research is to analyze using Islamic law the judge's decision regarding parental intervention in divorce at the Belopa Religious Court. The rise of divorce is because a third person who interferes in the marriage turns out to not only be an affair of one of the partners but it turns out that parents can also be that third party. by Where the party should be the first mediator in resolving household cases. The method used is qualitative with primary and secondary data sources. Data collection techniques include documentation, interviews and observation. The results of the research found that there were of the 436 cases there were several cases divorce in the Belopa Religious Court which were caused by parental interference. The judge's decision on a divorce case is made using the standard of Marriage Law Number 1 of 1974 as amended by Law Number 16 of 2019. And looking at the advantages and disadvantages, if the aspects to be united but there are more disadvantages then the judge decides to carry out a divorce, because don't let something that has a bigger impact emerge if they are put back together. On the other hand, if the benefit is greater then the judge will carry out mediation first and not decide whether there will be a divorce. Keywords: Parental Interference, Divorce, Judge's Decision